Deni Pengaruh Pemanfaatan Sosial Media, Motivasi Dan Pengetahuan Bisnis Terhadap Minat Berwirausaha (Studi Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Majalengka) - Nining Kurniasih; Deni Istiono; Pupung Pamungkas (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The role of entrepreneurship can have an influence on the economic improvement of a country, one of which is MSMEs. The better MSMEs in a country, the better the economic growth in that country. Against the background of low interest in entrepreneurship among students. This study aims to find out how the influence of Social Media Utilization, Motivation and Business Knowledge on Interest in Entrepreneurship in Students of the Faculty of Economics and Business, University of Majalengka. The method used is survey method with a verification descriptive approach. The population in this study were 6th and 8th semester students of the Faculty of Economics and Business, Majalengka University who had studied entrepreneurship courses, with a sample of 100 people. The instrument test used in this study is the validity and reliability test. The analytical tools used in this study are the classical assumption test, multiple linear regression analysis, analysis of the coefficient of determination and hypothesis testing for partial tests using the t test and simultaneous tests using the f test. The results showed that social media utilization was in the very high category, motivation was in the high category and business knowledge was in the very high category. The results of hypothesis testing show partially and simultaneously that social media utilization, motivation and business knowledge have a significant effect on entrepreneurial interest.